Early switching of tenofovir disoproxil fumarate (TDF) in HIV-infected patients with TDF-induced nephrotoxicity: a prospective study. Issue 1 (19th August 2022) - Patamatamkul, Samadhi; Songumpai, Nopporn; Payoong, Paruspak; Katavetin, Pisut; Putcharoen, Opass
Abstract : Background: Tenofovir disoproxil fumarate (TDF) can induce proximal renal tubulopathy (PRT) and necessitate changes in treatment regimen. This prospective study aimed to compare tubular function recovery following early switching versus late switching of TDF in human immunodeficiency virus (HIV)-infected patients with TDF-induced PRT. Methods: For this prospective study, conducted during 2017–2019, we enrolled HIV-1-infected, virologically suppressed adults undergoing TDF-containing combination antiretroviral therapy. Patients were separated into a late-switching group (LSG) and an early-switching group (ESG). The LSG included patients having an estimated glomerular filtration rate (eGFR) decrease ≥25% from the pretreatment level or Fanconi syndrome. The ESG included patients having ≥2 of the following indicators of PRT: fractional excretion of phosphate (FEUP) ≥10%, low tubular maximum reabsorption of phosphate (TmP)/GFR, or uricosuria; fractional uric acid excretion ≥10%; urine protein–creatinine index (UPCI) ≥500 mg/g creatinine, normoglycemic glycosuria, or decrease in eGFR of 15%–24%. Recovery of proximal tubular function at 6 and 12 months after TDF discontinuation was assessed. Complete recovery was defined as normalization of all abnormal tubular markers. Results: Thirty-three HIV-infected patients were enrolled (70% male). Except for tubular function markers, baseline characteristics were not significantly different between the two groups. The proportion of patients having complete recovery was significantly higher in the ESG ( p = 0.007, log-rank test). FEUP improved significantly in the ESG after TDF discontinuation; improvements of eGFR and UPCI were greater in the LSG. An eGFR change of 10% from baseline was the only independent predictor of failure to achieve complete recovery after switching. After median follow-up of 2.25 years post-trial, sustained recovery of eGFR within 5% of pre-TDF eGFR was achieved only in the ESG. Conclusions: Early-switching of TDF in HIV patients with PRT may allow complete recovery of proximal renal tubular function.